2021
DOI: 10.1080/23746149.2021.1918022
|View full text |Cite
|
Sign up to set email alerts
|

Tracking ultrafast reactions in organic materials through vibrational coherence: vibronic coupling mechanisms in singlet fission

Abstract: A multitude of ultrafast photoinduced reactions in organic semiconductors are governed by the close interplay between nuclear and electronic degrees of freedom. From biological light-harvesting and photoprotection to organic solar cells, the critical electronic dynamics are often precisely synchronized with and driven by nuclear motions, in a breakdown of the Born-Oppenheimer approximation. Ultrafast time-domain Raman methods exploit impulsive excitation to generate nuclear wavepackets and track their coherent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
41
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 171 publications
(288 reference statements)
0
41
0
4
Order By: Relevance
“…54 As a result, some form of symmetry breaking is responsible for the first fission step, S 1 -1 (TT), though the mechanism is debated. 35,36,55 As stated above, reported time constants for this first step range from 25 fs 35,36 to 2 ps. 33,34 Next, 1 (TT) separates into (TÁ Á ÁT) over tens of picoseconds, [33][34][35][36] a process thought to occur by thermally-activated triplet hopping.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…54 As a result, some form of symmetry breaking is responsible for the first fission step, S 1 -1 (TT), though the mechanism is debated. 35,36,55 As stated above, reported time constants for this first step range from 25 fs 35,36 to 2 ps. 33,34 Next, 1 (TT) separates into (TÁ Á ÁT) over tens of picoseconds, [33][34][35][36] a process thought to occur by thermally-activated triplet hopping.…”
Section: Introductionmentioning
confidence: 68%
“…54 As a result, some form of symmetry breaking is responsible for the first fission step, S 1 → 1 (TT), though the mechanism is debated. 35,36,55 As stated above, reported time constants for this first step range from 25 fs 35,36 to 2 ps. 33,34…”
Section: Introductionmentioning
confidence: 76%
“… [34] Bis‐PBI can be regarded as one of the simplest H‐aggregates so that we can rule out intimate conformational heterogeneity derived from long‐range molecular aggregates and resulting in complicated exciton dynamics. [ 13 , 34 ] Furthermore, we have utilized time‐resolved impulsive stimulated Raman spectroscopy (TR‐ISRS),[ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ] allowing us to capture vibrational snapshots at various time delays after photoexcitation, which includes the information on complete structural evolution from the initial Frenkel‐like exciton to the excimer state. Our time‐resolved Raman results prove that structural changes via the specific interchromophore vibrational coordinates, which have been theoretically suggested, actually pertain to the fate and nature of the excimer state.…”
Section: Introductionmentioning
confidence: 99%
“…The SF and TTA processes in Rub crystals and films are well reviewed in the recent papers by Bossanyi et al 13 , 14 It is now widely accepted that SF is a three-step process 15 where the initial step forms a correlated triplet state 1 (TT) later evolving into the 1 (T···T) state as it losses electronic coherence between triplets but retains the spin-0 character and subsequent spin decoherence results in full dissociation into free triplets. 16 , 17 The efficiency of the SF process strongly depends on the intermolecular coupling dictated by intermolecular distance, that is, an overlap of π-orbitals between neighboring molecules and relative intermolecular orientation. 18 Many reports have shown that the SF rate is mostly limited by triplet energy transport that allows dissociating the triplet pair.…”
Section: Introductionmentioning
confidence: 99%